Brazil : 2012 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Brazil. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
A strong policy framework and improved income distribution and social outcomes have been important accomplishments in Brazil. The 2012 Article IV Consultation highlights that financial stability in Brazil has been underpinned by a strong banking system and framework for regulation and supervision. Executive Directors have commended authorities' commitment to a strong policy framework, which has delivered a decade of macroeconomic stability and rising living standards. They have also welcomed the recent reorientation of the policy mix toward generating fiscal savings and providing monetary countercyclical support.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet